Numerical investigation of combined convective heat transfer using fractal barriers in a circular cavity filled with nanofluid - Reza Mougouei; Ali B.M. Ali; Omid Ali Akbari; Gholamreza Ahmadi; Soheil Salahshour; Sh Baghaei (Case Studies in Thermal Engineering)
In the present research, the numerical investigation of the nanofluid flow inside the circular cavity with the presence of fractal barriers has been done using the finite volume method (FVM). This investigation is done for Richardson numbers (Ri) = 0.1 to 1, solid nanoparticle volume fraction (φ) = 0 to 0.6 and for three shapes of fractal barrier in the two-dimensional (2D) cavity. The results of this research show that the presence of an obstacle with a special shape causes the components of the flow paths, creates weaker vortices in parts of the cavity and finally increases the contact of the fluid with hot surfaces. The behavior of the flow lines in the cavity is affected by two main stimulating factors. The main factor in the movement of the flow is the mobility of the cap (lid-driven), which, as a result, due to the viscosity of the fluid, the layered transfer of movement continues to the lower layers of the fluid. This factor forces the flow field to move. An increase in Ri increases the speed of the cap, which will result in better heat penetration and mixing between the fluid layers in different parts of the cavity. If this is accompanied by an increase in the disturbance of the flow due to the presence of obstacles, it will have a greater effect on the uniform temperature distribution. It seems that in addition to the forced convection, the conduction mechanism will also play a significant role in heat distribution. Adding solid nanoparticles in a higher φ, this behavior makes the heat distribution uniform to a small extent. Moreover, changing the shape of the fractal barrier will cause changes in fluid circulation behavior and reduce the slope of constant temperature lines. The thermal conductivity of the fluid will also improve through the addition of solid nanoparticles and consequently, the local Nusselt number (Nu) increases. Changes in the average Nusselt number at Ri = 0.1 in different volume fractions and for the cases studied can cause an increase in the Nusselt number between 10 and 16 percent. The above behavior for Ri = 1 improves the Nusselt number by less than 13 percent and for Ri = 10 this is less than 4 percent.